Comparative evaluation of staining efficacy of calcofluor white and acridine orange for detection of Candida species using fluorescence microscopy – A prospective microbiological study - Punjabi, Vishal (J Oral Maxillofac Pathol, 2020)
CONTEXT: Candida is a yeast-like fungus, and it causes candidiasis. Since it is commonly encountered in many cases, the need of the hour is for rapid and reliable method for identification of these fungi in tissue sections. AIM: The aim of this study was to evaluate and compare the staining efficacy of calcofluor white (CFW) and acridine orange (AO) for the detection of Candida species in formalin-fixed paraffin-embedded tissue samples of oral squamous cell carcinoma (OSCC) using fluorescence microscopy. SETTINGS AND DESIGN: Sample size comprised forty cases of OSCC. MATERIALS AND METHODS: Before tissue sampling, a swab of the area was taken, it was immediately inoculated on Sabouraud's dextrose agar media and germ tube test was performed for positive cultures for species identification. Tissue sections were obtained from cases of OSCC from the formalin-fixed paraffin-embedded tissue blocks of the same cases in which microbiological assessment was done at the time of tissue sampling, were stained with CFW and AO stain, respectively, and were examined using a fluorescent microscope. STATISTICAL ANALYSIS: Descriptive statistics were expressed in numbers and percentage. Independent t-test (unpaired t-test) and Chi-square test were used. P ≤0.05 was taken to be statistically significant. RESULTS: The mean number of microorganisms per high-power field stained by CFW and AO was 6.35 and 2.57, respectively, and a statistically significant difference (P ≤ 0.001) was observed. CFW compared to swab culture gave P = 0.018, which showed a statistically significant association. CONCLUSIONS: CFW is a better fluorescent stain when compared to AO to detect Candida species in tissue sections of OSCC cases.